2016
DOI: 10.1016/j.aap.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

What happens when drivers face hazards on the road?

Abstract: The current study aims to obtain knowledge about the nature of the processes involved in Hazard Perception, using measurement techniques to separate and independently quantify these suspected subprocesses: Sensation, Situation Awareness (recognition, location and projection) and Decision-Making. It applies Signal Detection Theory analysis to Hazard Perception and Prediction Tasks. To enable the calculation of Signal Detection Theory parameters, video-recorded hazardous vs. quasi-hazardous situations were prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…Many people are optimistic and tend to expect things to be positive (Sharot, 2011, Sharot, Guitart-Masip, Korn, Chowdhury, & Dolan, 2012, Sharot, Riccardi, Raio, & Phelps, 2007, so they may tend to mistakenly detect hazards that present in unattended periphery as no danger, while what is actually happening is they just don't see the hazards. Similar results have been found in previous studies where drivers showed conservative criteria in hazard detection regardless of driving experience (Ventsislavova et al, 2016;Wallis & Horswill, 2007). Hazard detection is a special detection task, because the penalty for a miss and a false alarm is different: a miss may cause a crash, while a false alarm may only lead to unnecessary brakes; thus, the criterion in hazard detection task is closely related with driving safety.…”
Section: Discussionsupporting
confidence: 87%
“…Many people are optimistic and tend to expect things to be positive (Sharot, 2011, Sharot, Guitart-Masip, Korn, Chowdhury, & Dolan, 2012, Sharot, Riccardi, Raio, & Phelps, 2007, so they may tend to mistakenly detect hazards that present in unattended periphery as no danger, while what is actually happening is they just don't see the hazards. Similar results have been found in previous studies where drivers showed conservative criteria in hazard detection regardless of driving experience (Ventsislavova et al, 2016;Wallis & Horswill, 2007). Hazard detection is a special detection task, because the penalty for a miss and a false alarm is different: a miss may cause a crash, while a false alarm may only lead to unnecessary brakes; thus, the criterion in hazard detection task is closely related with driving safety.…”
Section: Discussionsupporting
confidence: 87%
“…Many people are optimistic and tend to expect things to be positive (Sharot, 2011;Sharot, Guitart-Masip, Korn, Chowdhury, & Dolan, 2012;Sharot, Riccardi, Raio, & Phelps, 2007), so they may tend to mistakenly detect hazards that present in unattended periphery as no danger, while what is actually happening is they just don't see the hazards. Similar results have been found in previous studies where drivers showed conservative criteria in hazard detection regardless of driving experience (Ventsislavova et al, 2016;Wallis & Horswill, 2007). Hazard detection is a special detection task, because the penalty for a miss and a false alarm is different: a miss may cause a crash, while a false alarm may only lead to unnecessary brakes; thus, the criterion in hazard detection task is closely related with driving safety.…”
supporting
confidence: 87%
“…in a hazardous situation was found to depend on the driver's experience. This extends beyond research that has previously compared novice and experienced drivers (Crundall, 2016, Jackson et al, 2009Lim, Sheppard and Crundall, 2014) and demonstrates that this skill develops across a wider spectrum of experience than we may have first thought, from learner, through to highly experienced (see also Castro et al, 2014;Ventsislavova et al, 2016). As this predictive skill underlies the whole hazard avoidance process (Pradhan and Crundall, 2017), and is therefore crucial to safe driving (Horswill and McKenna, 2004), it follows that authorities should make efforts to improve hazard prediction in novice and learner drivers.…”
Section: Experience Affects Hazard Predictionmentioning
confidence: 85%